'Time to Wake Up': Climate change advocacy in a polarized Congress, 1996-2015. Issue 4 (7th June 2021) - Guber, Deborah Lynn; Bohr, Jeremiah; Dunlap, Riley E.
ABSTRACT: Scholars who study the failure of climate change policy in the United States tend to focus on the mechanics of denial and the coordinated efforts of political operatives, conservative think tanks, and partisan news outlets to cast doubt on what has become overwhelming scientific consensus. In contrast, we address a factor that has been understudied until now – the role of climate change advocacy in the U.S. Congress. Using quantitative text analysis on a corpus of floor speeches published in the Congressional Record between 1996 and 2015, we find notable differences in the language partisans use. Democrats communicate in ways that are message-based, emphasizing the weight of scientific evidence, while Republicans tend towards a softer, cue-based narrative based on anecdotes and storytelling. We end with a discussion of what climate change advocates can hope to accomplish through the 'politics of talk, ' especially in an age of heightened polarization.